Cooperative, ATP-dependent Association of the Nucleotide Binding Cassettes during the Catalytic Cycle of ATP-binding Cassette Transporters - Moody, Jonathan E. (2002)
ATP-binding cassette (ABC) transporters harvest the energy present in cellular ATP to drive the translocation of a structurally diverse set of solutes across the membrane barriers of eubacteria, archaebacteria, and eukaryotes. The positively cooperative ATPase activity (Hill coefficient, 1.7) of a model soluble cassette of known structure, MJ0796, from Methanococcus jannaschii indicates that at least two binding sites participate in the catalytic reaction. Mutation of the catalytic base in MJ0796, E171Q, produced a cassette that can bind but not efficiently hydrolyze ATP. The equivalent mutation (E179Q) in a homologous cassette, MJ1267, had an identical effect. Both mutant cassettes formed dimers in the presence of ATP but not ADP, indicating that the energy of ATP binding is first coupled to the transport cycle through a domain association reaction. The non-hydrolyzable nucleotides adenosine 5′-(β,γ-imino)triphosphate and adenosine 5′-3-O-(thio)triphosphate were poor analogues of ATP in terms of their ability to promote dimerization. Moreover, inclusion of MgCl(2), substitution of KCl for NaCl, or alterations in the polarity of the side chain at the catalytic base all weakened the ATP-dependent dimer, suggesting that electrostatic interactions are critical for the association reaction. Thus, upon hydrolysis of bound ATP and the release of product, both electrostatic and conformational changes drive the cassettes apart, providing a second opportunity to couple free energy changes to the transport reaction.